2011
DOI: 10.1111/j.1469-8137.2011.03997.x
|View full text |Cite
|
Sign up to set email alerts
|

Divergent evolution of oxidosqualene cyclases in plants

Abstract: Summary• Triterpenes are one of the largest classes of plant metabolites and have important functions. A diverse array of triterpenoid skeletons are synthesized via the isoprenoid pathway by enzymatic cyclization of 2,3-oxidosqualene. The genomes of the lower plants Chlamydomonas reinhardtii and moss (Physcomitrella patens) contain just one oxidosqualene cyclase (OSC) gene (for sterol biosynthesis), whereas the genomes of higher plants contain nine to 16 OSC genes.• Here we carry out functional analysis of ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
151
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(166 citation statements)
references
References 98 publications
(196 reference statements)
15
151
0
Order By: Relevance
“…Phylogenetic analysis of an isoarborinol synthase (IAS) from Oryza sativa (rice) demonstrated that it was recently derived from a plant cycloartenol synthase (6). Our analysis demonstrates that E. adriatica EUS is phylogenetically distinct from O. sativa IAS and most likely was not acquired via horizontal gene transfer from a plant source.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Phylogenetic analysis of an isoarborinol synthase (IAS) from Oryza sativa (rice) demonstrated that it was recently derived from a plant cycloartenol synthase (6). Our analysis demonstrates that E. adriatica EUS is phylogenetically distinct from O. sativa IAS and most likely was not acquired via horizontal gene transfer from a plant source.…”
Section: Discussionmentioning
confidence: 83%
“…has the pentacyclic structure similar to a bacterial hopanoid (23). Various hopanoid, sterol, and plant triterpenoid synthases have been characterized, including a rice isoarborinol synthase (IAS) (6). However, a microbial enzyme that cyclizes oxidosqualene in the CBC conformation to an arborinol lipid has yet to be identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This will open up opportunities to carry out functional analysis in planta using reverse genetics, with the aim of identifying mutations in UGT74H5, UGT74H6, and other target genes of interest and assessing the role of these genes in specialized metabolism, plant defense, and other important crop traits. UGT74H5 and UGT74H6 now form part of the growing tool kit of characterized genes and enzymes available from plants that can be deployed for triterpene metabolic engineering for disease control and synthetic biology applications (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…For example, β-amyrin synthase and cycloartenol synthase from P. ginseng (Kushiro et al 1998), five OSCs from Kalanchoe daigremontiana (Wang et al 2010), dammaranediol synthase from Centella asiatica (Kim et al 2009), β-amyrin synthase from Aster sedifolius and Arabidopsis thaliana (Shibuya et al 2009) and OSC from Aster tataricus and tomato (Wang et al 2011;Sawai et al 2011), have been cloned and functionally characterized in mutant yeast strain GIL77, having lanosterol synthase deficiency. The catalytic functions of several plants OSCs have been studied using the S. cerevisiae yeast mutants and Pichia pastoris strains (Kajikawa et al 2005;Ito et al 2011;Xue et al 2012;Sun et al 2013). Confalonieri et al (2009) over-expressed the Aster sodifolius β-amyrin synthase (AsOXA1) in Medicago truncatula and observed significantly higher amount of some triterpenes accumulation in leaf and roots.…”
Section: Introductionmentioning
confidence: 99%